2021
DOI: 10.3390/ijms222313170
|View full text |Cite
|
Sign up to set email alerts
|

(20S) Ginsenoside Rh2 Exerts Its Anti-Tumor Effect by Disrupting the HSP90A-Cdc37 System in Human Liver Cancer Cells

Abstract: (20S) ginsenoside Rh2 (G-Rh2), a major bioactive metabolite of ginseng, effectively inhibits the survival and proliferation of human liver cancer cells. However, its molecular targets and working mechanism remain largely unknown. Excitingly, we screened out heat shock protein 90 alpha (HSP90A), a key regulatory protein associated with liver cancer, as a potential target of (20S) G-Rh2 by phage display analysis and mass spectrometry. The molecular docking and thermal shift analyses demonstrated that (20S) G-Rh2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 59 publications
0
9
0
Order By: Relevance
“…Some examples have demonstrated that different ginsenosides active ingredients have anti-tumor effect in various cancers. 41 , 42 However, gisenosides and osteoclast differentiation also have a strong correlation. Gisenosides prevent osteoporosis by inhibiting osteoclast differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Some examples have demonstrated that different ginsenosides active ingredients have anti-tumor effect in various cancers. 41 , 42 However, gisenosides and osteoclast differentiation also have a strong correlation. Gisenosides prevent osteoporosis by inhibiting osteoclast differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…80,81 (20S) ginsenoside Rh2 has been identified as a major active substance of ginseng and has significant anticancer activity. 82 In 2020, Wang et al found that ANXA2 interacted with NF-κB p50 subunit and facilitated NF-κB activation to boost the expression of mesenchymal-like genes, cell motility and EMT transition in triple-negative breast cancer cells 76 (Figure 1).…”
Section: Anxa2 and Other Cytokines Implicated In Emtmentioning
confidence: 99%
“…The lncRNA‐MUF colocalize with ANXA2 in the cytoplasm of HCC cells to promote ANXA2 combination with glycogen synthase kinase 3β (GSK3β), and accelerate the EMT pathway activation through Wnt/β‐catenin signaling 80,81 . (20S) ginsenoside Rh2 has been identified as a major active substance of ginseng and has significant anticancer activity 82 . In 2020, Wang et al found that ANXA2 interacted with NF‐κB p50 subunit and facilitated NF‐κB activation to boost the expression of mesenchymal‐like genes, cell motility and EMT transition in triple‐negative breast cancer cells 76 (Figure 1).…”
Section: How Does Anxa2 Participate In Epithelial‐mesenchymal Transit...mentioning
confidence: 99%
“…The bioactive compounds in ginseng include approximately 30 triterpene glycosides, called ginsenosides (Rb1, Rb2, Rg1, Rg2, Rg3, Rc, Rd, Re, Rh1, Rh2, etc.) [135,136]. Among the glycosides, Rg3, Rd, and Rh2 have anti-tumor activity.…”
Section: Ginsenoside Rh2 (Grh2)mentioning
confidence: 99%